Dossier II: Radicalismo en Cataluña: Análisis del discurso de la diada - Pérez Álvarez, Alejandro (Quadernos de criminología, 2020)
Analysis of the speech of the President of the Generalitat of Catalonia. Using the models of Rodríguez-Carballeira (1992) and McCauley and Moskalenko (2008) with the aim to study the presence of factors and mechanisms of indoctrination and radicalization. Finding these factors especially those of the cognitive sphere. Concluding that the message emitted is similar to those that can be observed in the sects.